Analisis Pengaruh Thin Capitalization dan Transaksi Afiliasi terhadap Agresivitas Pajak (Studi pada Perusahaan Multinasional Sektor Manufaktur) - Marwah Multaraffi Muhammad; Herry Laksito (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of thin capitalization and related-party transactions on tax aggressiveness in multinational manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The background of this research is based on the financial complexity of multinational firms, which allows flexibility in managing financing structures and intra-group transactions, thereby increasing the potential for tax aggressiveness. Thin capitalization reflects a high proportion of debt relative to equity, while related-party transactions represent the intensity of economic relationships among affiliated entities within a corporate group. This research employs a quantitative approach using secondary data obtained from corporate financial statements. The sampling technique used is purposive sampling, resulting in 84 observations. Data analysis is conducted using multiple linear regression, preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Tax aggressiveness is measured using the Effective Tax Rate (ETR), while thin capitalization is proxied by the debt-to-equity ratio, and related-party transactions are measured by the proportion of affiliated transactions to total sales. The results indicate that both partially and simultaneously, thin capitalization and related-party transactions significantly influence tax aggressiveness. These findings suggest that debt-based financing structures and the intensity of affiliated transactions play a crucial role in corporate tax planning strategies. This study contributes empirically to the taxation literature and provides insights for regulators in strengthening policies to monitor and control tax avoidance practices among multinational corporations in Indonesia.